Peran Aktor Pengamanan Keefektian Penganggaran: Studi Etnometodologi Di Sektor Publik - Husna, Sabna Daniela; Krisno Septyan (Politeknik Ganesha Medan, 2024)
This study aims to understand the meaning of the role of the Program and Budget Head in maintaining budget effectiveness at the Cilandak District office. This research took place in the Cilandak District office. Data were obtained through source triangulation and data triangulation. Source triangulation was carried out through interviews with the Head of Programs and Budgets and the Spending Treasurer. Meanwhile, data triangulation was obtained through the Budget Implementation Document (DPA) and the 2020 & 2021 Budget Realization Report. This researcher uses an ethnomethodological approach. The use of ethnomethodology aims to see the routines of the Head of Programs and Budgets in budgeting. The results of the study show that the preparation of the budget is quite good and effective, but cooperation between Heads of Sections is still needed in absorbing the budget, and if budget absorption is still below 91% it will have an impact on performance appraisal in the coming fiscal year.